2017
DOI: 10.1016/j.shaw.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Leukocyte Subsets and Expressions of FcγR and Complement Receptors among Female Ragpickers in Eastern India

Abstract: BackgroundThere are a million ragpickers in India who gather and trade recyclable municipal solid wastes materials for a living. The objective of this study was to examine whether their occupation adversely affects their immunity.MethodsSeventy-four women ragpickers (median age, 30 years) and 65 age-matched control housemaids were enrolled. Flow cytometry was used to measure leukocyte subsets, and leukocyte expressions of Fcγ receptor I (CD64), FcγRIII (CD16), complement receptor 1 (CD35) and CR3 (CD11b/CD18),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Hematological tests had shown increased white blood cells suggesting inflammation and allergic reactions among SW workers. 25 Biochemical tests among ragpickers had shown that their occupation adversely affects immunity, 40 even causing cytological and genotoxic damage 41 which leads to cancer. Significant airway inflammation was found among women ragpickers making them more vulnerable to chronic diseases compared to a control group of women.…”
Section: Documented Various Types Of Dermatologicalmentioning
confidence: 99%
“…Hematological tests had shown increased white blood cells suggesting inflammation and allergic reactions among SW workers. 25 Biochemical tests among ragpickers had shown that their occupation adversely affects immunity, 40 even causing cytological and genotoxic damage 41 which leads to cancer. Significant airway inflammation was found among women ragpickers making them more vulnerable to chronic diseases compared to a control group of women.…”
Section: Documented Various Types Of Dermatologicalmentioning
confidence: 99%
“…Feeling discriminated against and compelled to work as ragpickers to earn their livelihoods, and enduring monotony and repetitiveness on-the-job in addition to pain, bruises, lacerations, abrasions, burns, sprains, headaches, breathlessness, fever (Ojha et While most of the papers focusing on health have examined both male and female ragpickers, Mondal et al (2016Mondal et al ( , 2017, Fulwani et al (2020) and Uplap et al (2014) have focused only on the latter. Mondal et al (2016Mondal et al ( , 2017 have noted that the health of malnourished female ragpickers in Kolkata (and in general, anywhere in the world) who have been diagnosed with oxidative stress, inflammation, blood platelet hyperactivity, genotoxicity and anaemia, is further exacerbated if they avail of wood, dung or charcoal as cooking fuel. Fulwani et al (2020) and Kandasamy et al (2013) have pointed out that a majority of the ragpickers (male and female) can often afford just one meal every day.…”
Section: Topical -What?mentioning
confidence: 99%
“…The developing world is still far away from embracing the paradigm of gender parity. Female ragpickers -girls and women -lead an extremely challenging existence and some authors have focused on them in their research (Joshi 1998;Mondal et al 2016;Mondal et al 2017;Saikia 2019;Fulwani et al 2020), and urged municipal/private healthcare agencies to monitor their health on a regular basis and provide adequate advice. Focusing on the well-being of women in general is verily a lynchpin for sustainable development; and attaining the SDGs.…”
Section: Who Are Being Addressed and Why?mentioning
confidence: 99%
“…These vulnerabilities of women waste workers are insufficiently examined in scholarship on gender, labor, informal work, the waste economy, and health systems. Research on the health and well-being of women waste workers is mostly limited to a few discrete studies on occupational health and safety (16)(17)(18). There is a dearth of relational, intersectional, and contextual research that explores and understands the health and well-being concerns and embodied experiences of women waste workers.…”
Section: What We Foundmentioning
confidence: 99%